Integrating Cloud Storage in STEM Education: A Case Study on Collaborative Project-Based Learning - Imomova, Umida; Tleuzhanova, Manatzhan; Sattorova, Zilola; Khaydarova, Mahliyo; Doniyarov, Mavlonbek; Nasritdinova, Umida; Saidov, Madilkhan (Malikussaleh University, Aceh, Indonesia, 2025)
When science, technology, engineering, and mathematics (STEM) are combined, these topics provide children with the knowledge and skills they need to become intelligent, responsible adults. The primary teaching approach used in this research was Project-Oriented Problem-Based Learning (Po-PBL), which examined the effects of an integrated STEM education system on students' 21st-century competencies. A one-group quasi-experimental methodology and polling techniques were used to assess the students' understanding before and after the program began. The findings demonstrated that pupils' overall 21st-century abilities significantly improved. This was particularly true for their production skills, which improved from mediocre to excellent. Because Po-PbL requires students to focus on real-life issues and discover answers, it is evident that it is particularly beneficial for students in STEM areas. The research emphasizes the value of incorporating Po-PbL into STEM education to assist students in improving their problem-solving, creativity, teamwork, and communication skills. When students work on projects with their hands, they use what they already know and discover new things. These abilities will help students deal with a challenging situation in the future.